SISTEM KENDALI SERVO POSISI dan KECEPATAN MOTOR dengan PROGRAMMABLE LOGIC CONTROL (PLC) - Andani Andani; Christoforus Y; Iqbal Zakariah; Asifa Nurul Husnah (Foristek, 2011)
The simulation of controlled position dan speed servo motor using Programmable Logic Control (PLC), done by comparate input and output voltage from practical and theory. Controlling position of servo motor has error 2.24% till 22.22% while controlling speed between 0.67% till 2.92%.